(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aimed to analyze the role of strategic planning in improving security performance within the Saudi Ministry of Interior. This was achieved by exploring the extent of the application of strategic methods in security operations and evaluating their impact on improving operational efficiency and effective responses to security challenges. The study also aimed to provide recommendations that would contribute to enhancing the effectiveness of strategic planning to achieve the Kingdom’s Vision 2030 in the security field. The study relied on a descriptive analytical approach, where data was collected from theoretical and field sources, through analyzing previous literature and conducting questionnaires directed at Ministry of Interior employees. Statistical methods were also used to analyze the data and draw conclusions that reflect the reality of strategic planning in the security sector. The study concluded that the Saudi Ministry of Interior widely applies strategic planning, which contributes to improving security performance and raising operational efficiency. The results also revealed challenges that hinder the effectiveness of strategic planning, such as limited coordination between various security agencies and the limited use of some modern technologies in security analysis. The study confirmed that developing a strategic planning system contributes to improving security decision-making processes and enhancing preparedness to confront potential security crises.